6(4x-5)(4x+3)=0

Simple and best practice solution for 6(4x-5)(4x+3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(4x-5)(4x+3)=0 equation:


Simplifying
6(4x + -5)(4x + 3) = 0

Reorder the terms:
6(-5 + 4x)(4x + 3) = 0

Reorder the terms:
6(-5 + 4x)(3 + 4x) = 0

Multiply (-5 + 4x) * (3 + 4x)
6(-5(3 + 4x) + 4x * (3 + 4x)) = 0
6((3 * -5 + 4x * -5) + 4x * (3 + 4x)) = 0
6((-15 + -20x) + 4x * (3 + 4x)) = 0
6(-15 + -20x + (3 * 4x + 4x * 4x)) = 0
6(-15 + -20x + (12x + 16x2)) = 0

Combine like terms: -20x + 12x = -8x
6(-15 + -8x + 16x2) = 0
(-15 * 6 + -8x * 6 + 16x2 * 6) = 0
(-90 + -48x + 96x2) = 0

Solving
-90 + -48x + 96x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '6'.
6(-15 + -8x + 16x2) = 0

Factor a trinomial.
6((-3 + -4x)(5 + -4x)) = 0

Ignore the factor 6.

Subproblem 1

Set the factor '(-3 + -4x)' equal to zero and attempt to solve: Simplifying -3 + -4x = 0 Solving -3 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -4x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -4x = 0 + 3 -4x = 0 + 3 Combine like terms: 0 + 3 = 3 -4x = 3 Divide each side by '-4'. x = -0.75 Simplifying x = -0.75

Subproblem 2

Set the factor '(5 + -4x)' equal to zero and attempt to solve: Simplifying 5 + -4x = 0 Solving 5 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -4x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -4x = 0 + -5 -4x = 0 + -5 Combine like terms: 0 + -5 = -5 -4x = -5 Divide each side by '-4'. x = 1.25 Simplifying x = 1.25

Solution

x = {-0.75, 1.25}

See similar equations:

| 2-7(x+1)=3(x-2)-5(x+3) | | 756x^18= | | (3x+8)=(5x-2) | | y-1=.5x-7 | | 5x+2=4x+2 | | 7(5+n)=42 | | 45x-37y+87-7+3x= | | 12x=29.9 | | 2y-8=y+4 | | 5n+n=3n-2+2(2n+1) | | 2+8lnx=26 | | 24.4-4p=53.3 | | 15+3x+6=-7x+2x+2 | | 12r^2+21r-8r-14=0 | | 2x+2=-5x+23 | | 6x+11=2x+47 | | 16a+3= | | y-5=0x-7 | | p(x)=[x-(1+2i)][x-(1-2i)](x-2)(x+1) | | 3xy+7x+6x+8xy= | | p=-12.5t+100 | | 0.5y+0.2y=0.3y+2 | | 13-1(2x+4)=35 | | 3.1x+2=-0.5 | | 15+-8=x | | 4(2x-3)(4x+5)=0 | | 6(a+2)-2(2a+5)=18 | | 12x^2+24x-288=0 | | (7x+16)+(9x-12)=180 | | 15x+3x=180 | | 9t+-21=3(t+-7)+6t | | 4(3x+1)+4=13x+4 |

Equations solver categories